Acute effect of electrical muscle elongation and static stretching in hamstring muscle extensibility - Espejo-Antúnez, L.; López-Miñarro, P.A.; Albornoz-Cabello, M.; Garrido-Ardila, E.M. (Science & Sports, 2016)
Objective: The acute effect of electrical muscle elongation (EME) versus static stretching (SS) on hamstring extensibility was analyzed. Material and methods: Sixty-three adult athletes with reduced hamstring flexibility (straight leg raise test angle < 80°) were randomly assigned to: group 1 (one EME session of 4 kHz interferential current, bipolar technique and AMF = 100 Hz, n = 21), group 2 (one set of SS, n = 21) or group 3 (control group, n = 21). The hamstring muscle extensibility was assessed immediately before and after the intervention with the passive knee extension test. Results: Significant improvements (p < 0.05) were found in both EME (+10.09°) and SS (+8.61°) groups whereas no significant changes were detected in control group (+0.09°). Although no significant differences were found between EME and SS groups, the EME group showed large effect size (d = 0.927) while SS group reached medium effect size (d = 0.571). Conclusions: The use of electrical muscle stimulation in adult athletes with restricted hamstring extensibility can achieve immediate improvements in hamstring extensibility, slightly higher than those gained with static stretching.